Pengaruh Persepsi Harga, Promosi, Kualitas Produk, Gaya Hidup, dan Citra Merek terhadap Pembelian Motor Vespa Matic LX di Kota Tegal - Rizqi Roman Azmi; Rauly Sijabat; Ika Indriasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The development of the automotive industry, especially automatic motorcycles in Indonesia, is increasingly rapid and triggers fierce competition between manufacturers, including Piaggio with the Vespa Matic LX product which has a unique design, elegant image, and different characteristics from other automatic motorcycles. This study aims to analyze the influence of price perception, promotion, product quality, lifestyle, and brand image on the interest in buying Vespa Matic LX in people in Tegal City. The research approach uses quantitative methods with survey techniques. The study population is the people of Tegal City who use or own a Vespa Matic LX, and because the population is unknown, the sample determination uses the Lemeshow formula so that 100 respondents were obtained. Data analysis included instrument tests, classical assumption tests, and multiple linear regressions with the help of IBM SPSS Statistics 22. The results showed that all variables—price perception, promotion, product quality, lifestyle, and brand image—had a positive and significant effect on purchase interest. These findings confirm that the management of the right marketing strategy in terms of price, promotion, quality, lifestyle, and brand image can increase consumer interest in the Vespa Matic LX. This research provides important implications for companies in formulating marketing strategies that are more effective and oriented to consumer needs.